The hunchback assignments / 1. - Slade, Arthur G. (Arthur Gregory) (Hunchback assignments, 2009)
In Victorian London, fourteen-year-old Modo, a shape-changing hunchback, becomes a secret agent for the Permanent Association, which strives to protect the world from the evil machinations of the Clockwork Guild.